From sign to symbol : transformational processes in psychoanalysis, psychotherapy, and psychology - Newirth, Joseph (Psychodynamic psychotherapy and assessment in the twenty-first century., 2018)
From Sign to Symbol describes emerging approaches to the unconscious experience and the development of emotional meaning in intersubjective, implicit relationships. He presents strategies that utilize symmetrical, impactful interventions in psychoanalysis, psychotherapy, and psychotherapy supervision through a combination of insights from contemporary psychoanalysis, neuropsychology, and cognitive and developmental psychology.